AB0472 INFECTIOUS PROFILE IN PATIENTS WITH ANCA-ASSOCIATED VASCULITIS: RETROSPECTIVE ANALYSIS IN A REFERRAL CENTRE. (13th June 2020) - Estévez Gil, M.; Maure, B.; Argibay, A.; Vazquez-Triñanes, C.; Gimena, B.; Rivera, A.
Abstract : Background: The antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) are rare multisystem autoimmune diseases of unknown cause, characterised by inflammatory cell infiltration causing necrosis of blood vessels. The treatment of AAV requires prolonged immunosuppressive therapy. Infections remain a major cause of morbidity and mortality. Objectives: The aim of our study was to investigate the prevalence and characteristics of infection, and analyse the factors associated with infection in patients with AAV from Northern of Spain. Methods: Retrospective, descriptive study of patients with AAV followed in a specific Systemic Autoimmune Diseases and Thrombosis Unit from January 2000 to December 2019. Demographic, laboratory, microbiology, treatment and clinical data were collected from the medical records. AAV was diagnosed according to the definitions of the Chapel Hill nomenclature and designated as granulomatosis with polyangiitis (GPA), eosinophilic granulomatosis with polyangiitis (EGPA), microscopic polyangiitis (MPA) or pauci-immune necrotizing and/or crescentic glomerulonephritis without systemic vasculitis (renal-limited vasculitis, RLV). Disease activity of AAV was evaluated by Birmingham Vasculitis Activity score (BVAS). The infection episode was considered on the basis of clinical, laboratory, microbiology, radiology information, and response to therapy. Different episodes of infection in one patient were independently reflected. Data were analysed using SPSS 25.0 Results: Thirty-six patients of which 20 (55.6%) were males. Median follow-up was 42 months. The mean age at the diagnosis was 61.14 ± 17.49 years and mean BVAS was 18.81 ± 5.96. 15 patients were diagnosed of GPA, 13 of MPA, 5 of EGPA and 3 of RLV. 72.2% MPO, 11.1% PR3. Lung involvement occurred in 75% of patients, upper airways was detected in 41.7%, skin involvement in 16.7%, Nervous system affectation occurred in 33.3%. 30 patients (83.3%) had renal affectation with a mean of 1.93± 1.66 gr/dl of Proteinuria and 2.9±2.17mg/dl of creatinine. We detected hypocomplementemia in 27.8% of patients (C3 in 19.4% and C4 in 16.7%). Regarding induction treatments, all patients received corticoids at high doses, 21 (58.3%) Cyclophosphamide, 3 (20%) Rituximab and 2 (13.3%) patients, Azathioprine. When we analyse infections, we detected 15 patients (41.66%) who presented any infection after the diagnosis of AAV, with a total of 71 episodes of infection. The most frequent were bacterial infections (29 episodes), specifically gram negative pathogens. The most frequent location was the respiratory (56.3%) followed by urinary (22.5%) and Skin (8.5%). Also opportunistic infections were described: 3 patients with Aspergillus fumigatus and one patient with Cryptococcus neoformans. 41 of these episodes needed hospitalisation with a median stay of 11 days. 6 episodes warranted intensive care unit (ICU) admission. Infection related mortality was 2.82%. We made latent tuberculosis screening and Pneumocystis prophylaxis in all our patients. No cases of Tuberculosis or Pneumocystis were recorded. Factors associated with increased risk of hospitalisation with statistical signification in univariated study were MPA, Hypocomplementemia and increased BVAS. But in the logistical regression study, only the value of the BVAS maintained statistical significance. The only factor associated with elevated risk of ICU admission was IgG deficit in the multivariate analysis. Neither immunosuppressive therapy nor age was associated with increased risk of infection in our study. Conclusion: More than 50% of the episodes of infection needed hospitalisation in patients with AAV. Risk factors for hospitalisation and ICU admission were BVAS and IgG deficit respectively. Bacterial infections were the most frequent but fungal infections were the most severe. Disclosure of Interests: None declared